Race and the Decision to Seek the Death Penalty in Federal Cases, 1995-2000 (United States) - Klein, Stephen P. ([Verlag nicht ermittelbar], 2006)
The purpose of this project was to examine possible defendant and victim race effects in capital decisions in the federal system. Per the terms of their grant, the researchers selected cases that were handled under the revised Death Penalty Protocol of 1995 and were processed during Attorney General Janet Reno's term in office. The researchers began the project by examining a sample of Department of Justice Capital Case Unit (CCU) case files. These files contained documents submitted by the United States Attorney's Office (USAO), a copy of the indictment, a copy of the Attorney General's Review Committee on Capital Cases (AGRC's) draft and final memorandum to the Attorney General (AG), and a copy of the AG's decision letter. Next, they created a list of the types of data that would be feasible and desirable to collect and constructed a case abstraction form and coding rules for recording data on victims, defendants, and case characteristics from the CCU's hard-copy case files. The record abstractors did not have access to information about defendant or victim gender or race. Victim and defendant race and gender data were obtained from the CCU's electronic files. Five specially trained coders used the case abstraction forms to record and enter salient information in the CCU hard-copy files into a database. Coders worked on only one case at a time. The resulting database contains 312 cases for which defendant- and victim-race data were available for the 94 federal judicial districts. These cases were received by the CCU between January 1, 1995 and July 31, 2000, and for which the AG at the time had made a decision about whether to seek the death penalty prior to December 31, 2000. The 312 cases includes a total of 652 defendants (see SAMPLING for cases not included). The AG made a seek/not-seek decision for 600 of the defendants, with the difference between the counts stemming mainly from defendants pleading guilty prior to the AG making a charging decision. The database was structured to allow researchers to examine two stages in the federal prosecution process, namely the USAO recommendation to seek or not to seek the death penalty and the final AG charging decision. Finally, dispositions (e.g., sentence imposed) were obtained for all but 12 of the defendants in the database. Variables include data about the defendants and victims such as age, gender, race/ethnicity, employment, education, marital status, and the relationship between the defendant and victim. Data are provided on the defendant's citizenship (United States citizen, not United States citizen), place of birth (United States born, foreign born), offense dates, statute code, counts for the ten most serious offenses committed, defendant histories of alcohol abuse, drug abuse, mental illness, physical or sexual abuse as a child, serious head injury, intelligence (IQ), or other claims made in the case. Information is included for up to 13 USAO assessments and 13 AGRC assessments of statutory and non-statutory aggravating factors and mitigating factors. Victim characteristics included living situation and other reported factors, such as being a good citizen, attending school, past abuse by the defendant, gross size difference between the victim and defendant, if the victim was pregnant, if the victim had a physical handicap, mental or emotional problems or developmental disability, and the victim's present or former status (e.g., police informant, prison inmate, law enforment officer). Data are also provided for up to 13 factors each regarding the place and nature of the killing, defendant motive, coperpetrators, weapons, injuries, witnesses, and forensic and other evidence.